A laparoscopic technique for full thickness intestinal biopsy and feeding jejunostomy. - Eltringham, W K (1993)
A laparoscopic technique is described, suitable for both full thickness intestinal biopsy and placement of a feeding jejunostomy tube. Its application in three cases is reported. The method is simple, permits full laparoscopic examination of the abdominal contents and being minimally invasive, facilitates early patients recovery.